2013
DOI: 10.1103/physreve.87.012144
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Brayton cycle with coupled systems as working substance

Abstract: We explore the quantum version of the Brayton cycle with a composite system as the working substance. The actual Brayton cycle consists of two adiabatic and two isobaric processes. Two pressures can be defined in our isobaric process; one corresponds to the external magnetic field (characterized by F(x)) exerted on the system, while the other corresponds to the coupling constant between the subsystems (characterized by F(y)). As a consequence, we can define two types of quantum Brayton cycle for the composite … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 30 publications
(36 reference statements)
0
29
0
Order By: Relevance
“…In addition we compare our results with those similar studies of Heisenberg type interaction coupled spins. These studies showed the interaction enhanced work and efficiency [12,13,15,24,27,33], and elucidated the possibility of work extraction in the regimes inaccessible by the non-interacting working substances [12,13]; however they did not take into account anisotropy or LMG type coupling between the spins. Our results reveal unique advantages of anisotropy for enhancing cooperative work output, opening new working regimes, optimization of maximum work at optimal efficiency as well as bring practical advantages by extending the domain of interacting spin working substances to anisotropic systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition we compare our results with those similar studies of Heisenberg type interaction coupled spins. These studies showed the interaction enhanced work and efficiency [12,13,15,24,27,33], and elucidated the possibility of work extraction in the regimes inaccessible by the non-interacting working substances [12,13]; however they did not take into account anisotropy or LMG type coupling between the spins. Our results reveal unique advantages of anisotropy for enhancing cooperative work output, opening new working regimes, optimization of maximum work at optimal efficiency as well as bring practical advantages by extending the domain of interacting spin working substances to anisotropic systems.…”
Section: Introductionmentioning
confidence: 99%
“…QHEs can extract more work from heat baths relative to classical heat engines [4,5]; they can operate beyond the classical Carnot bound without breaking the second law by exploiting quantum resources; such as entangled [6] or quantum coherent heat reservoirs [7,8], or by regenerative steps [9]. In comparison to non-interacting working substances, such as a two level (qubit) [4,5] or a multilevel atom [10], or a simple harmonic oscillator [11], QHEs with interacting working substances, in particular coupled spins, are found to be more efficient and capable to harvest more work [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. Physical realizations of QHEs are proposed for a single ion [34,35], Paul trap [9], ultracold atoms [36], optomechanical systems [37], quantum dots [38], circuit and cavity quantum electrodynamic systems [7,39,40].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantum heat engines are typically based on implementations of quantum Carnot, Otto [15], Brayton [16,17], Diesel [16,18] or Stirling cycles [19,20], with a succession of strokes that alternatively extract work and exchange heat with the hot and cold reservoirs. As a result the generation of work is an intermittent process.…”
Section: Introductionmentioning
confidence: 99%